Frotteuristic disorder - a specific paraphilia - Krystian Wdowiak; Agnieszka Maciocha; Julia Wąż; Aleksandra Witas; Weronika Chachaj; Aleksandra Winsyk; Ewa Gardocka (Quality in Sport)
Introduction: Frotteuristic disorder is characterized by recurrent and intense sexual arousal from touching or rubbing against a nonconsenting person over a period of at least six months. This behavior is manifested through fantasies, urges, or actions. While many studies indicate that the disorder predominantly affects men, this finding is not universally accepted. Victims of this disorder are typically young women, but only 2.6% of incidents are reported to the police. Most individuals with frotteuristic disorder do not seek treatment voluntarily, often being referred only after committing a crime. Cognitive-behavioral therapy has shown significant therapeutic success, while pharmacological treatments typically involve antiandrogenic medications and drugs that lower sexual drive.